International political economy : state-market relations in the changing global order - Passe-Smith, John T., ed.; Conklin, John G., ed. (Boulder, London : Lynne Rienner Publishers, 1996)
Economics
Keywords: International finance; International political economy; Economic assistance; Monetary relations; World bank; International trade relations; International production